THE EFFECTIVENESS OF THE SAINTIFIC APPROACH IN IMPROVING STUDENT LEARNING RESULT 4 “TEMA INDAHNYA KEBERSAMAAN” IN ELEMENTARY SCHOOL PURWANTORO 1 MALANG - Nuzulia, Nuril (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The scientific approach is a learning process designed to enable students to learn actively by doing the 5 M process of observing, asking, trying, reasoning and communicating. Learning by using a scientific approach can encourage students to find out from various sources by making observations and not just receiving knowledge from teachers. The purpose of this study is to determine the effectiveness of scientific approach in improving student learning outcomes of grade 4 on the theme of togetherness in SDN Purwantoro 1 Malang. This research uses a quantitative approach with a simple experimental research type. Method in the form of observation, interviews, questionnaires and documentation. From the 4th graders of SDN Purwantoro 1 Malang, 2 classes were taken: experimental class and control class with 30 students. Data analysis used Independent t test with SPSS 16 tool. From the research result can know the average value of learning result of experiment class 88, mean while control class average learning result 80 and Sig 0,000 <0,05 hence Ho rejected, its mean there are differences in learning outcomes of the experimental class with the control class. So it can be concluded very effective approach can improve thematic learning theme beautiful together in SDN Purwantoro 1 Malang.